2016
DOI: 10.2147/opth.s97722
|View full text |Cite
|
Sign up to set email alerts
|

Epiretinal membrane: optical coherence tomography-based diagnosis and classification

Abstract: Epiretinal membrane (ERM) is a disorder of the vitreomacular interface characterized by symptoms of decreased visual acuity and metamorphopsia. The diagnosis and classification of ERM has traditionally been based on clinical examination findings. However, modern optical coherence tomography (OCT) has proven to be more sensitive than clinical examination for the diagnosis of ERM. Furthermore, OCT-derived findings, such as central foveal thickness and inner segment ellipsoid band integrity, have shown clinical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 81 publications
0
82
0
3
Order By: Relevance
“…13 In this study, an inflammatory etiology is suggested by the relative higher frequency of ERMs (8 of the 10 eyes) than PVD (4 of the 10 eyes) at diagnosis, as well as the frequent identification of posterior vitreous cells on OCT and of hyperreflective deposits (which may represent cellular debris) on the posterior hyaloid surface of eyes without PVD. Secondary ERM formation in inflammatory ocular disease is thought to be mediated by cytokines that promote proliferation of not only glial cells typically found in idiopathic ERMs but also leukocytes.…”
Section: Discussionmentioning
confidence: 76%
“…13 In this study, an inflammatory etiology is suggested by the relative higher frequency of ERMs (8 of the 10 eyes) than PVD (4 of the 10 eyes) at diagnosis, as well as the frequent identification of posterior vitreous cells on OCT and of hyperreflective deposits (which may represent cellular debris) on the posterior hyaloid surface of eyes without PVD. Secondary ERM formation in inflammatory ocular disease is thought to be mediated by cytokines that promote proliferation of not only glial cells typically found in idiopathic ERMs but also leukocytes.…”
Section: Discussionmentioning
confidence: 76%
“…A) (Stevenson et al. ). Epiretinal membrane (ERM) contracture can involve the centre of the macula, with flattening of foveal pit and other changes in the outer retinal layers.…”
Section: Resultsmentioning
confidence: 99%
“…Although the typical presentation of an ERM is metamorphopsia, the symptoms can range from asymptomatic to severely decreased visual acuity (VA) (Stevenson et al. ). The prevalence of ERM has been variously reported from 2.2% to 28.9%, depending on the population studied (You et al.…”
Section: Introductionmentioning
confidence: 99%